Effect of the ratio between non-structural carbohydrates and degradable protein of concentrate on milk yield and quality of grazing Cilentana goats - Grossi M.; Bovera F.; Piccolo V.; D'Urso S.; Cutrignelli M.I.; Infascelli F. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Forty-five Cilentana goats were equally divided into three groups that received, as pasture supplementation, three concentrates with a different NSC:degradable protein ratio: 0.84, 0.73 and 0.60, respectively for groups A, B and C. The concentrates were fed at 200, 300 and 400 g/head/d, and at 45, 30 and 15 days before lambing, respectively. Then, the quantities increased until 800 g/head/d. After two months from lambing, the lambs were sold; the milk yield was monitored monthly for 5 controls. Each time, individual milk samples were collected and analysed for protein, fat, lactose, non-protein nitrogen and casein. Group A showed significantly higher milk yields, averaged over the whole trial period (1.463 vs 1.343 vs 1.182 kg/d, respectively for groups A, B and C; P<0.01) and a lower non-protein nitrogen percentage (0.21 vs 0.24 and 0.23, respectively for groups A, B and C; P<0.01).
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)